Subject satisfaction following treatment with nanofractional radiofrequency for the treatment and reduction of acne scarring and rhytids: A prospective study. (24th September 2021) - Arruda, Suleima; Swearingen, Alyssa; Medrano, Kathleen; Sadick, Neil
Abstract: Background: Skin‐related changes, such as fine lines, wrinkles, and acne scarring, are a source of distress to both men and women. Nanofractional radiofrequency delivers thermal energy to skin layers leading to dermal remodeling that can address skin conditions related to aging. The objective of this study was to evaluate the subject satisfaction of nanofractional radiofrequency for the treatment of facial wrinkles and acne scarring in both lighter and darker skin tones. Materials and methods: 30 subjects (skin types II‐VI) were enrolled in this prospective, evaluator‐blind study. The average age of subjects was 51.9 ± 13.5 years. Subjects received three treatments at 3‐ to 5‐week intervals on both sides of the face using the 80‐ or the 160‐pin tip disposables. Follow‐up visits were conducted at 6‐ and 12 weeks after the last treatment. Subject satisfaction was evaluated using a self‐assessment of a reduction of wrinkles or acne scars, and subject satisfaction questionnaire. Pain, tolerability, and safety were monitored throughout. Results: Subjects treated for acne or wrinkles were satisfied with their treatment at both the 6‐week and 12‐week follow‐up visit (mean score 3.0; range 0 = very unsatisfied to 4 = very satisfied). The treatments were well tolerated at all treatment sessions, averaging a score of 3.5 on the tolerability scale (0 = very intolerable to 4 = very tolerable) with treatment‐associated pain reported to be mild (3.2 out of 10). There were no adverse events or unanticipated side effects. Conclusions: This clinical study demonstrates subjects are satisfied with nanofractional radiofrequency treatments for improvement of their wrinkles and acne scars.